International Community Service: Animal Welfare Campaign And Education For Elementary Student In Kota Bharu, Kelantan, Malaysia - Dian Ayu Kartika Sari; Desty Apritya; Moh. Noor Rahman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The existence of animals has a very important role in the lives of children around the world who generally place animals as their closest friends. Having pets for children provides benefits in the form of social support, reducing stress levels and can increase empathy for other living things. Children who love their pets will usually become someone who is aware of the importance of animal welfare and most importantly has a humane character. Animal Welfare Education for children at the elementary school level aims to provide early prevention of animal abuse and improve humane character. Therefore, this Community Service aims to provide early education to children at the elementary school level about the importance and how to apply animal welfare values in everyday life, which in the long term will bring goodness and benefits to human health and welfare.